2022
DOI: 10.1080/07853890.2022.2085317
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of assessment tools in arthroscopic training: a systematic review

Abstract: Background Multiple assessment tools are used in arthroscopic training and play an important role in feedback. However, it is not fully recognized as to the standard way to apply these tools. Our study aimed to investigate the use of assessment tools in arthroscopic training and determine whether there is an optimal way to apply various assessment tools in arthroscopic training. Methods A search was performed using PubMed, Embase and Cochrane Library electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Despite some critical comments [13, 36], many studies have shown that arthroscopic skills can not only be learned and trained on the simulator [5, 9, 10, 14, 32] but also objectively and reliably tested using skill scores [3, 8, 20, 24, 26, 30, 31, 39]. Although simulator training will never replace training in the operating theatre, it allows the measurement and documentation of the learning progress and is ideally suited to implement proficiency‐oriented skill training.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some critical comments [13, 36], many studies have shown that arthroscopic skills can not only be learned and trained on the simulator [5, 9, 10, 14, 32] but also objectively and reliably tested using skill scores [3, 8, 20, 24, 26, 30, 31, 39]. Although simulator training will never replace training in the operating theatre, it allows the measurement and documentation of the learning progress and is ideally suited to implement proficiency‐oriented skill training.…”
Section: Introductionmentioning
confidence: 99%